Demonstrating the effect of forensic firearm countermeasures: Bullet characteristics generated due to barrel modifications. (December 2015) - O'Keeffe, C.; Champion, S.; Allsop, D.
Highlights: Typical barrel modifications are examined to determine their effect on bullet striations. Macroscopic examination of fired bullets. Fired bullets demonstrated that each modification imparts a distinguishable characteristic. Abstract: Forensic awareness and the declining availability of firearms have resulted in an increase in the use of modified and re-activated firearms in crime. Although some modifications are undertaken to simply acquire a functioning firearm, others are perpetrated as a direct forensic countermeasure to prevent the association between a firearm and a crime. This article describes the effects of these modifications on bullet striation patterns imparted from the barrel to a fired bullet. The key results indicated that the investigated modifications display assessable characteristics. The use of an oversized barrel imparted striations consistent with firing with the absence of typical rifling. Subsequent or consecutively fired bullets possessed striation variations, with the first showing the least evidence of striations. The application of a choke resulted in more obvious bullet elongation compared to a smoothbore barrel. The restriction caused merging of lands and groves of the imparted rifling and obscured their usual definition. Effects of breech adaption were also characterised by observing the buckling and enlargement of the cartridge case. This deformity of the cartridge case was most evident when the barrel pressure increased due to the presence of the choke. From this study it was evident that unique characteristic impressions associated with different modifications most commonly found in criminal investigations can be utilised by a forensic expert and impart significant intelligence to an investigation.